Total and structure colonization by arbuscular mycorrhizal fungi in native, perennial grasses of different forage quality exposed to defoliation - Ambrosino, Mariela L. (2018)
Defoliation can compromise the quality and quantity of colonization by arbuscular mycorrhizal fungi (AMF), which contribute to vegetation persistence in semiarid rangelands. The effects of defoliation on total arbuscular mycorrhizal (AM) colonization percentage and on that of its structures (i.e., vesicles, arbuscules) were evaluated on three native, rangeland perennial grass species. These species (i.e., Poa ligularis, Nassella tenuis and Amelichloa ambigua) show different palatability to domestic livestock in Central Argentina. In August 2012, soil + roots (0–10 cm depth) were sampled below the foliage of 12 plants of each species. Half of the plants were then defoliated to 5 cm stubble leaving active meristems intact after defoliation. The other half remained undefoliated. In September, immediately after the differentiation of apical meristems from vegetative to reproductive, soil + roots samples were again obtained and thereafter plants were once again defoliated. The final soil + root sampling was conducted in October (6 plants/species/treatment). The study was repeated on a different plant set during 2013. The percentage of total AM colonization and that its structures were determined. Palatable species did not reach a greater total colonization by AMF in their roots than A. ambigua. Treatments affected the total colonization only at some sampling times (e.g., when it did affect at N. tenuis, the effect of defoliation was not consistent during the study years). At the last date, A. ambigua showed a greater percentage of arbuscules in both defoliation treatments in 2012 and on defoliated plants in 2013. In general, P. ligularis showed a greater vesicle percentage than the other species. Management practices which allow the recuperation of the perennial grasses after a moderate grazing, will not affect considerably their symbiotic relationships.